The performance and amphibious operation potential of a new floating photovoltaic technology. (June 2022) - Kjeldstad, Torunn; Nysted, Vilde S.; Kumar, Manish; Oliveira-Pinto, Sara; Otnes, Gaute; Lindholm, Dag; Selj, Josefine
Highlights: Analysis of one year of production and monitoring data from new FPV technology. Performance comparison between floating PV system and nearby ground-mounted PV. U-value of 33 W/m 2 K calculated based on measured weather and production data. Stable performance after dry period indicates possibility of amphibious operation. Abstract: Floating photovoltaics (FPV) is a rapidly emerging technology that provides an alternative to ground-mounted PV (GPV), particularly where land is scarce or expensive. Despite an impressive technological development and growth in installed capacity in recent years, studies on the performance and reliability of FPV are scarce. This work provides insight with respect to the performance, reliability, and operational characteristics of a new FPV technology with the aim to identify innovation opportunities, reduce risks, develop improved solutions, and improve bankability of FPV. We have analysed production and weather data from one year of operation for an open FPV system with a small water footprint located on a water body in Kilinochchi, Sri Lanka. The technology is developed by the company Current Solar. Using established filtering routines and algorithms from pvlib, the yield and performance ratio is calculated and compared to a GPV system installed on the shore of the lake. We find that the technology gives a stable overall performance over the one-year period, and that the period of amphibious operation did not impact the continued performance of the system. Calculations of the U-value of the system, based on the production and weather data, gives a median U-value of 33 W/m 2 K, slightly higher than the default PVsyst value of 29 W/m 2 K for freestanding GPV systems. The calculated U-values are used in an energy yield analysis in PVsyst to estimate the energy production of the FPV technology and benchmark it against measured data.